Enhancing shoulder strength through blood flow restriction training: a systematic review and meta-analysis - Hamedi, H.; Gholipour, M. A.; Seyedhoseinpoor, T. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Blood flow restriction training (BFRT) has emerged as a promising way to enhance strength and build muscle with low-load exercises. This study was aimed to evaluate the effects of upper limb BFRT on shoulder strength.